Oxygen uptake in water polo, comparison and agreement in cycle ergometer and eggbeater kick: A pilot study - Ligia Ignêz Engelmann; Giane Veiga Liedtke; Flávio de Souza Castro
Abstract The aim of this study was to compare and verify the agreement of maximal oxygen uptake (VO2 max) values obtained from tests on land and in water. Twelve recreational water polo players (30.5 ± 7.7 years; 79.2 ± 7.2 kg body mass; 179.1 ± 5.9 cm height) were assessed in two phases: (1) in laboratory with maximal test on a cycle ergometer and (2) in a swimming pool with maximal test in eggbeater kick. Maximum values obtained in the two tests (respectively, cycle ergometer, and eggbeater kick: VO2 max = 40.2 ± 2.7 ml.kg-1.min-1 and 38.4 ± 5.7 ml.kg-1.min-1; RER = 1.17 ± 0.08 and 1.19 ± 0.12; HR max = 181.4 ± 11.7 bpm and 179 ± 11.7 bpm; IEP = 20 and 20) did not show significant differences. According to the Bland-Altman analyses, there were acceptable limits of agreement between the two tests (land and water). Therefore, it can be concluded that the eggbeater kick test is a specific and valid protocol to asses VO2 max in water polo players.